COMPREHENSIVE PUBLIC SMOKING PROGRAM # PUBLIC AFFAIRS - BROZEK, MICHAEL; NELSON, DAN (Tufts Archival Research Center, 2007)
Marginalia; Confidential; Memorandum from Michael Brozek and Dan Nelson to Walter Woodson regarding a response to a memo concerning public affairs initiatives on the indoor air quality issue. Talks about the ACVA and their importance in media presentations and one-on-one discussions with legislators.